Nutritional care is a human right: Translating principles to clinical practice. (23rd May 2022) - Cárdenas, Diana; Davisson Correia, Maria Isabel T.; Hardy, Gil; Ochoa, Juan B.; Barrocas, Albert; Hankard, Régis; Hannequart, Isabelle; Schneider, Stéphane; Bermúdez, Charles; Papapietro, Karin; Pounds, Teresa; Cuerda, Cristina; et al.
Abstract: We have previously advocated that nutritional care be raised to the level of a human right, in close relationship to two well‐recognized fundamental rights: the right to food and the right to health. This article aims to analyze the implication of nutritional care as a human right for healthcare practitioners. We will focus on the impact of the Human Rights Basic Approach (HRBA) on healthcare professionals (HCPs), namely how they can translate HRBA into routine clinical practice. Ethics and human rights are guiding values for clinical nutrition practitioners. Together they ensure a patient‐centered approach, in which the needs and rights of the patients are of the most significant importance. Human rights are based on the powerful idea of equal dignity for all people while expressing a set of core values, including fairness, respect, equality, dignity, and autonomy (FREDA). Through the analysis of FREDA principles, we have provided the elements to understand human rights and how an HRBA can support clinicians in the decision‐making process. Clinical practice guidelines in clinical nutrition should incorporate disease‐specific ethical issues and the HRBA. The HRBA should contribute to building conditions for HCPs to provide optimal and timely nutritional care. Nutritional care must be exercised by HCPs with due respect for several fundamental ethical values: attentiveness, responsibility competence, responsiveness, and solidarity.